2015
DOI: 10.3171/2014.10.spine1498
|View full text |Cite
|
Sign up to set email alerts
|

Laminoplasty versus laminectomy and fusion for multilevel cervical myelopathy: a meta-analysis of clinical and radiological outcomes

Abstract: OBJECT Posterior cervical surgery, expansive laminoplasty (EL) or laminectomy followed by fusion (LF), is usually performed in patients with multilevel (≥ 3) cervical spondylotic myelopathy (CSM). However, the superiority of either of these techniques is still open to debate. The aim of this study was to compare clinical outcomes and postoperative kyphosis in patients undergoing EL versus LF by performing a meta-analysis. ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 16 publications
5
48
0
Order By: Relevance
“…There was no significant difference in JOA and VAS scores, with the assessment of CCI revealing comparable outcomes between the two surgical approaches. These results were consistent with a prior review and meta-analysis [23], which concluded that LF and EL lead to equivalent clinical improvement and loss of lordosis. The authors included that there is no evidence to support EL over LF in the treatment of multi-level CSM; however, the relative complication rates between the two approaches was not clearly established.…”
Section: Discussionsupporting
confidence: 93%
“…There was no significant difference in JOA and VAS scores, with the assessment of CCI revealing comparable outcomes between the two surgical approaches. These results were consistent with a prior review and meta-analysis [23], which concluded that LF and EL lead to equivalent clinical improvement and loss of lordosis. The authors included that there is no evidence to support EL over LF in the treatment of multi-level CSM; however, the relative complication rates between the two approaches was not clearly established.…”
Section: Discussionsupporting
confidence: 93%
“…A 2015 meta-analysis demonstrated that some loss of lordosis occurs following LF and laminoplasty, with similar clinical outcomes from either procedure. 21 Another study examined the role of sagittal alignment in precluding laminoplasty, with no correlation between sagittal alignment and outcome. 11 The reasons for these discordances are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Laminoplasty is an option for decompressing multilevel cervical spinal canal stenosis. [16,25] Some reports have recommended laminoplasty without fusion as a better option in patients with multilevel spinal stenosis and/or cervical lordosis. [2628] Even if the laminoplasty has a restrictive effect on intervertebral mobility regarding the decreased range of motion of the cervical spine, [29,30] the results of laminoplasty without spinal fusion for CSM in patients with ACP are unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%